Mapping Business Plan Studies Over a Quarter-Century: A Bibliometric Analysis - Fajar Syah Faizal Sinuraya; Keni Kaniawati (Ann Publisher, 2026)
This study examines the development and intellectual structure of business plan research over a twenty-five-year period using a bibliometric approach. Business plan studies have expanded significantly across entrepreneurship, small and medium-sized enterprises, and higher education, creating a fragmented and increasingly multidisciplinary body of knowledge. The aim of this research is to systematically map publication trends, influential contributors, thematic structures, and temporal shifts in business plan scholarship. Bibliographic data were retrieved from the Scopus database using the TITLE-ABS-KEY search query “business plan,” covering journal articles published between 2001 and 2025. Following a PRISMA-based screening process, 369 open-access articles were analyzed using VOSviewer and Biblioshiny. The results show a strong growth trajectory, with the field reaching a mature stage characterized by thematic diversification rather than decline. Influential publications and authors are concentrated in specific national contexts, particularly where entrepreneurship education and SME development are policy priorities. Thematic analysis reveals stable foundational themes alongside emerging topics related to innovation, sustainability, and artificial intelligence. The findings indicate that business plan research has evolved from a static planning orientation toward a dynamic, strategic, and learning-centered perspective. This study provides a comprehensive overview of the field’s evolution and offers insights for future academic research, educational practice, and entrepreneurship policy development.